Benefits of Psychological Detachment From Work: Does Autonomous Work Motivation Play a Role? - Olafsen, Anja Hagen; Bentzen, Marte (Frontiers in Psychology, 2020)
Research has shown that psychological detachment from work during nonwork time is beneficial for various aspects of employee well-being and job performance. However, it is uncertain whether psychological detachment is equally important to all. The purpose of the current study was to examine whether psychological detachment is less important for employees who experience autonomous motivation for their job. The hypotheses were tested in two different samples of knowledge-intensive firms in Norway. Latent profile analysis was used to identify different subgroups within the samples. In addition, the BCH method was used to examine possible differences between the profiles on distal outcomes. In both samples, two distinct profiles were found: “Lower involvement employees” (Low-IE; higher detachment and lower autonomous regulation) and “Higher involvement employees” (High-IE; lower detachment and higher autonomous regulation). The results revealed that the High-IE profile was significantly higher in positive affect, life satisfaction, work effort, and work quality, while significantly lower on emotional exhaustion compared with Low-IE. These results indicate that being low in detachment from work does not seem to be detrimental when combined with high levels of autonomous motivation. The study contributes to knowledge about the benefits of unwinding from work for employees with different motivational profiles.